Electro-detection of the antibacterial metronidazole using zinc oxide nanoparticles formed on graphitic carbon sheets. Analytical application: Human serum and urine - Jallal. Zoubir (KeAi Communications Co., Ltd., 2021)
Metronidazole is a highly effective active antibacterial against trichomoniasis and protozoan infections. A ZnO nanoparticle-modified graphite carbon paste electrode was constructed as an electrochemical sensor for the electroanalysis of metronidazole. The electro-catalytic properties of the ZnO@CPE electrode were examined by cyclic voltammetry and EIS. Zinc oxide nanoparticles synthesized on graphite carbon nanosheets by thermal route under studied and optimized experimental conditions were found to have excellent electro-catalytic performance for the reduction of metronidazole traces. The relationship between pH and Epc gave a slope of −59 mV/ZnO@CPE in the pH range of 4.5 to 9.5. Reflecting that the number of electrons and protons participating in the reaction convert the ϕ-NO2 attractor groups of Metronidazole molecules on the electro-catalytic surface of the fabricated electrode are equal. The morphology analysis of the fabricated electrode surface indicates the formation of zinc oxide crystals, the XRD study confirms the crystal structure of the hexagonal phase of ZnO. The calibration curve was constructed by the differential pulse voltameter method in the concentration range of 0.8–100 µmol L−1, with a limit of detection and limit of quantification of metronidazole equal to 1.018 10−7 M and 3.395 10−7 M respectively. The proposed method has been successfully tested for the detection of trace amounts of metronidazole in real samples such as urine and serum. The proposed method is also simple, fast and inexpensive. It has a good recovery rate, good selectivity and high sensitivity.